Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Berkarya Melalui Sampah Di SDN Banua Anyar 9 - Amalia Rizkina; Adetya Nor Rizkyka (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2025)
The aim of this research is to address observed issues in schools where the surroundings appear unclean with scattered litter. Poor management practices serve as a warning to take concrete actions towards creating a clean, comfortable, and waste-free school environment. Based on this, SDN Banua Anyar 9 implemented "P5 Berkarya Melalui Sampah" (P5 Creating Through Waste). Data collection methods included observation, file collection, and interviews with P5 project leaders and participating teachers at SDN Banua Anyar 9. Additionally, documentation included photos of student activities during the P5 implementation. The stages involved in applying the "P5 Berkarya Melalui Sampah" project at SDN Banua Anyar 9 were: 1) Introduction; 2) Contextualization; 3) Action; 4) Reflection and Follow-up. Results indicated significant student achievements in producing original works in the dimensions of faith and piety towards God, ethics towards nature including environmental preservation showing significant progress. In the creative dimension, producing original works and actions showed significant development. In the cooperation dimension, teamwork goals showed significant progress. The project successfully strengthened the student profile in Pancasila values through waste creativity at SDN Banua Anyar 9, evident in thorough planning, execution aligned with planning, and student achievements indicating substantial development.